Does the Type of MRI Sequence Influence Perceived Quality and Measurement Consistency in Investigations of the Anatomy of the Velopharynx?. (June 2022) - Perry, Jamie L.; Haenssler, Abigail E.; Kotlarek, Katelyn J.; Chen, Joshua Y.; Fang, Xiangming; Guo, Yifan; Mason, Kazlin; Webb, Michael
Purpose: The purpose of this study was to evaluate perceived image quality, confidence in identifying key velopharyngeal landmarks, and reliability of making velopharyngeal measures between 3-dimensional (3-D) and 2-D magnetic resonance imaging (MRI) methods and between T1-, T2-, and proton density (PD)-weighted sequences. Methods: Twelve healthy participants completed an MRI study. Three raters assessed overall image quality and their ability to identify key anatomic features within the images. A single rater evaluated the reliability of making measures between imaging methods and sequence types to determine if image type (2-D and 3-D) or image sequence (T1, T2, PD weighted) resulted in different values for key velopharyngeal landmarks. Results: An analysis of variance test revealed image quality was rated significantly different based on the scan type ( P < .001) and the sequence used ( P = .015). Image quality was rated higher among 2-D MR images compared to 3-D, and higher among T2 sequences compared to T1- and PD-weighted imaging methods. In contrast, raters favored 3-D sequences over 2-D sequences for identifying velopharyngeal landmarks. Measures of reliability revealed scan type significantly impacted 2 of the 6 variables but to a minimal degree; however, sequence type had no impact on measures of reliability across all variables. Conclusion: Results of the study suggest the scan type and sequence used are factors that likely do not impact the reliability of measures. Based on image quality, the recommended technique for velopharyngeal imaging would be using a 2-D T2-weighted technique. However, based on the ability to identify key landmarks, a 3-D T1- or PD-weighted technique was favored.